Recent technical advancements in ARPES: Unveiling quantum materials - Lim, Chan young; Kim, Sunghun; Jung, Sung Won; Hwang, Jinwoong; Kim, Yeongkwan (Current Applied Physics, 2024)
The technical evolution of angle-resolved photoemission spectroscopy (ARPES) in the late 90s played a pivotal role in the exploration of electronic structures in condensed matter systems. ARPES achieved numerous successes during this period, notably capturing the first evidence of the unconventional d-wave symmetry of the superconducting gap in cuprate superconductors. It also elucidated the essential rules governing topological signatures in the electronic structures of topological materials, and played an essential role in demonstrating the engineered band structures of atomically thin materials. These early achievements spurred significant advancements in the technique. This topical review delves into four cutting-edge ARPES techniques that are currently at the forefront of development: time-resolved ARPES, nano ARPES, in-situ ARPES, and ARPES with novel control parameters. By examining the capabilities of these innovative approaches, we aim to illustrate their potential in unlocking new frontiers and providing unprecedented insights on the electronic structure of quantum materials.
Keywords: Angle resolved photoemission spectroscopy; In-situ surface doping; Molecular-beam epitaxy; Nano angle-resolved photoemission spectroscopy; Surface doping; Time-resolved; Time-resolved angle-resolved photoemission spectroscopy; Uniaxial strains; Angle-resolved photoemission spectroscopy; In-situ surface doping; Molecular beam epitaxy; Nano ARPES; Time-resolved ARPES; Uniaxial strain